2015
DOI: 10.3389/fnhum.2015.00170
|View full text |Cite
|
Sign up to set email alerts
|

What makes you think you are conscious? An agnosticist manifesto

Abstract: The qualitative character of consciousness, its “what-it-is-likeness”, is a contested issue, both in philosophy and psychology. I argue that, rather than by conceptual analyses, the status of “what-it-is-likeness” has to be decided by empirical investigation. Pending the outcome, we should maintain an agnostic stance, in order to remove the bias in favor of fictionalism from our study of consciousness,. I illustrate this with the notion of “ownership unity”. People adhere to the belief of a single, unified sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
(94 reference statements)
0
5
0
Order By: Relevance
“…It is important to note however, that while our framework naturally accommodates the unity of experience, it is agnostic as far as the experience of unity goes (Welshon, 2013 ; Bennett and Hill, 2015 ; van Leeuwen, 2015 ): many facets of the content of our experience are “unified” in one sense or another, whether in objects, across different sensory modalities, or in seemingly more fundamental ways such as perspectivalness and even selfhood. However, as both brain-damaged patients and the effects of psychoactive drugs demonstrate (Shanon, 2002 ; Welshon, 2013 ; Bennett and Hill, 2015 ; van Leeuwen, 2015 ), such variants of content unity likely arise from specific mechanisms and do not constitute necessary aspects of experience, whereas unity in its barest form is simply synonymous with there being something it is like to undergo it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note however, that while our framework naturally accommodates the unity of experience, it is agnostic as far as the experience of unity goes (Welshon, 2013 ; Bennett and Hill, 2015 ; van Leeuwen, 2015 ): many facets of the content of our experience are “unified” in one sense or another, whether in objects, across different sensory modalities, or in seemingly more fundamental ways such as perspectivalness and even selfhood. However, as both brain-damaged patients and the effects of psychoactive drugs demonstrate (Shanon, 2002 ; Welshon, 2013 ; Bennett and Hill, 2015 ; van Leeuwen, 2015 ), such variants of content unity likely arise from specific mechanisms and do not constitute necessary aspects of experience, whereas unity in its barest form is simply synonymous with there being something it is like to undergo it.…”
Section: Discussionmentioning
confidence: 99%
“… 2 This is not to be confused with the experience of unity (Welshon, 2013 ; van Leeuwen, 2015 ; and see Section Discussion). …”
mentioning
confidence: 99%
“…Some of Kim"s interests included history and world facts. He was also fascinated by movie trivia, sports facts, geography, the space programme, actors and actresses, the bible, church history, classical music and literature (Hutchinson, 2013;Van Leeuwen, 2015).…”
Section: Kim Peekmentioning
confidence: 99%
“…Functional studies have now largely confirmed the correlation between coordinated patterns of GNW activity and waking consciousness (Baars et al 2013;Dehaene et al 2014), although the implementation of conscious awareness and consciously-directed activity is by no means settled (e.g. Block et al 2014;Graziano 2014;Hoffman and Prakash 2014;Tononi and Koch 2015;van Leeuwen 2015). While it is standard to conceptualize the GNW as a network of functionally-coherent anatomical regions connected by white-matter tracts (e.g.…”
Section: Background: the Gnw As An Swn Of Swnsmentioning
confidence: 99%